3D-Printed Microfluidic Automation - Au, Anthony K. (Lab Chip, 2015)
Microfluidic automation – the automated routing, dispensing, mixing, and/or separation of fluids through microchannels – generally remains a slowly-spreading technology because device fabrication requires sophisticated facilities and the technology’s use demands expert operators. Integrating microfluidic automation in devices has involved specialized multi-layering and bonding approaches. Stereolithography is an assembly-free, 3D-printing technique that is emerging as an efficient alternative for rapid prototyping of biomedical devices. Here we describe fluidic valves and pumps that can be stereolithographically printed in optically-clear, biocompatible plastic and integrated within microfluidic devices at low cost. User-friendly fluid automation devices can be printed and used by non-engineers as replacement for costly robotic pipettors or tedious manual pipetting. Engineers can manipulate the designs as digital modules into new devices of expanded functionality. Printing these devices only requires the digital file and electronic access to a printer.